"TRACKING THE DIGITAL PREDATOR: A STUDY ON CYBERSTALKING THROUGH CYBER LAW, FORENSIC SCIENCE, AND CRIMINAL INVESTIGATION" - Vyas Shivangi Anilkumar; Dr. Prakashkumar Thakor (International Educational Journal of Science and Engineering, 2025)
In the ever-evolving digital age, the boundaries of personal space and safety have been dramatically redefined. The internet, while serving as a powerful tool for communication, commerce, and information sharing, has simultaneously become a breeding ground for various forms of cybercrime. Among these, cyberstalking emerges as a particularly insidious threat. Unlike traditional stalking, which is physically observable and limited by geography, cyberstalking enables perpetrators to intrude into the personal lives of victims relentlessly, anonymously, and from any location across the globe. This study undertakes a comprehensive examination of cyberstalking, focusing on its legal, forensic, and investigative dimensions, to provide a multi-disciplinary understanding of how digital predators operate and how they can be effectively tracked and prosecuted. Cyberstalking is defined as the repeated use of electronic communication tools to harass, threaten, or intimidate an individual, group, or organization. The phenomenon often involves the use of emails, social media platforms, GPS tracking, instant messaging apps, and even sophisticated spyware or malware. Victims may suffer from psychological trauma, including anxiety, depression, and post-traumatic stress, and may also face reputational damage, social withdrawal, and economic losses. The anonymity afforded by digital platforms emboldens offenders, who exploit loopholes in privacy settings and data-sharing practices to track and manipulate their targets. Consequently, cyberstalking presents complex challenges to victims, law enforcement agencies, and legal practitioners alike. From a legal standpoint, cyberstalking occupies a unique position at the intersection of privacy rights, freedom of speech, and digital surveillance. This study delves into the legislative frameworks across multiple jurisdictions, with an emphasis on Indian cyber law as codified in the Information Technology Act, 2000 (with subsequent amendments), and relevant sections of the Indian Penal Code (IPC). It compares Indian legal provisions with international statutes such as the United States’ Violence Against Women Act (VAWA), the UK’s Protection from Harassment Act, and Australia’s Online Safety Act. The comparative legal analysis identifies key gaps, strengths, and areas requiring reform in cyberstalking legislation, particularly in addressing cross-border jurisdictional issues, procedural delays, and victim protection mechanisms. The study advocates for a harmonized international legal approach and robust victim support infrastructure. The role of forensic science in tackling cyberstalking has grown increasingly crucial with the advent of advanced digital forensic techniques. Digital forensics serves as the bridge between criminal behavior and actionable evidence. This study explores various technical methods used to trace and document cyberstalking behavior, such as IP address tracing, metadata analysis, forensic imaging of digital devices, recovery of deleted data, and examination of social media interactions. It also highlights the use of artificial intelligence and machine learning in detecting patterns of stalking behavior across large datasets. The study presents real-life case studies where forensic experts have successfully tracked down cyberstalkers through sophisticated methods, underscoring the importance of trained personnel, inter-agency coordination, and adequate infrastructure. Moreover, this research examines the standard operating procedures followed during a criminal investigation into cyberstalking. Investigative agencies often face significant challenges, including lack of jurisdictional clarity, encrypted communications, the volatility of digital evidence, and delays in obtaining data from service providers. The study outlines the procedural steps from filing a complaint to obtaining a conviction, including FIR registration, digital evidence seizure, chain-of-custody maintenance, witness examination, and presentation of forensic findings in court. It critically assesses the performance of cybercrime cells in India and other nations, emphasizing the need for capacity-building, public-private partnerships, and community outreach.